Piecewise-constant optimal control strategies for controlling the outbreak of COVID-19 in the Irish population - Náraigh, Lennon Ó; Byrne, Áine (Mathematical biosciences, 2020)
We introduce a deterministic SEIR model and fit it to epidemiological data for the COVID-19 outbreak in Ireland. We couple the model to economic considerations — we formulate an optimal control problem in which the cost to the economy of the various non-pharmaceutical interventions is minimized, subject to hospital admissions never exceeding a threshold value corresponding to health-service capacity. Within the framework of the model, the optimal strategy of disease control is revealed to be one of disease suppression, rather than disease mitigation. •Presentation of SEIR-type model for COVID-19, model fitted to data for Ireland.•Aim is to find best strategy for non-pharmaceutical interventions (NPIs).•Optimal-control theory is performed on the model; cost function: cost of the NPIs.•State constraint: Hospital admissions remain below a threshold.•Suppression is cheaper than mitigation, over a 1-year time horizon.